Testicular function in boys with 47,XYY and relationship to phenotype - Davis, Shanlee M (Am J Med Genet C Semin Med Genet, 2020)
An additional Y chromosome occurs in ~1 in 1,000 males, resulting in the karyotype 47,XYY. The phenotype includes tall stature, hypotonia, neuropsychiatric comorbidities, and an increased risk of infertility in adulthood. Little is known about testicular function in childhood and adolescence in 47,XYY. This cross-sectional study aimed to assess testicular function serum biomarkers, including total testosterone, inhibin B, and anti-mullerian hormone (AMH), in 82 boys with XYY (11.3 ± 3.8 years) compared with 66 male controls (11.6 ± 3.8 years). The association of testicular hormones with physical features, neuropsychological phenotype, and magnetoencephalography (MEG) was assessed with multiple linear regression models. Results indicate males with XYY have significantly lower inhibin B (median 84 pg/ml vs. 109 pg/ml, p = .004) and higher AMH (median 41 ng/ml vs. 29 ng/ml, p = .011); however, testosterone, testicular volume, and stretched penile length were not different from controls. In the exploratory analysis of relationships between hormone concentrations and phenotypic assessments, higher inhibin B concentrations were positively correlated with lower BMI and better cognitive, academic, and behavioral outcomes in the XYY group. Testosterone concentrations were positively associated with better behavioral outcomes in boys with XYY. Higher testosterone and inhibin B concentrations were also associated with shorter auditory latencies measured using magnetoencephalography (MEG) in XYY. With a few exceptions, testicular hormones were not associated with phenotypic outcomes in controls. In conclusion, there is evidence of subtle impaired testicular function in boys with XYY and a newly described relationship between measures of testicular function and some aspects of the XYY phenotype.